(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The study aimed to investigate the psychometric properties of the Adaptive Behavior Scale by applying it to children with cerebral palsy accompanied by intellectual disabilities, in order to provide a suitable tool for measuring adaptive behavior in a sample of individuals with cerebral palsy and comorbid intellectual disabilities. The sample consisted of 40 children aged 8 to 10 years with cerebral palsy and intellectual disabilities, noting that their motor disability was concentrated in the lower limbs (legs) rather than the upper limbs (arms). The study adopted the experimental method, as it aligns with the research objectives and hypotheses. The researcher utilized the following tools: the Adaptive Behavior Scale (developed by the researcher). The study yielded the following results: The validity indicators of the scale demonstrated its ability—based on its variables—to measure adaptive behavior in children with cerebral palsy accompanied by intellectual disabilities.